Penerapan Program “Makan Rendang” sebagai Strategi Pemerintah Kabupaten Tanah Datar untuk Meminimalisir Ketergantungan UMKM Terhadap Rentenir - Febrilia, Irma; Helmi, Rahmadhona Fitri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the supporting and inhibiting factors for the implementation of the Rendang Eating Program for MSMEs as a flagship program for the Tanah Datar Regency Regional Government. In this research, the researcher used a qualitative descriptive method where the aim of this method was to describe things that happened according to the conditions when the research was carried out. Data collection techniques in this research are interviews and documentation. Data were analyzed using reduction techniques, data presentation and drawing conclusions. The research results show that the implementation of the Rendang Eating Program has supporting factors, including First, the existence of clear regulations, with the latest legal basis, namely Regent's Regulation Number 1 of 2022. This regulation provides clear guidance and framework for all parties involved, including local government, KUKMP Service, Bank Nagari and Community. Second, full support from regional governments can also be seen through adequate budget allocation and good coordination between agencies. The inhibiting factors include First, there are still many people involved in BI-Cheking which causes these people to not be able to take advantage of the program. Second, the Rendang Meal Program has not been properly socialized to the public, so there are still many people who do not know about this program and the budget for the Rendang Meal Program itself has not been fully realized.